On Bergson’s Concept of the Virtual - Brian Hulse (Gamut: Online Journal of the Music Theory Society of the Mid-Atlantic, 2008)
The purpose of this essay has been to come to a better understanding of Bergson’s concept of the virtual, particularly as it is developed and understood by Deleuze, to argue that a precedent exists for the virtual as a valid analytic category, and to suggest a possible avenue of further research.